“Cave-in” decompression under unilateral biportal endoscopy in a patient with upper thoracic ossification of posterior longitudinal ligament: Case report - Jing, Xiaowei; Gong, Zhiyuan; Qiu, Xiaowen; Zhong, Zhuolin; Ping, ZiChuan; Hu, Qingfeng (Frontiers in Surgery, 2023)
Background Thoracic ossification of the posterior longitudinal ligament (TOPLL) requires surgery for spinal cord decompression. Traditional open surgery is extremely invasive and has various complications. Unilateral biportal endoscopy (UBE) is a newly developed technique for spine surgery, especially in the lumbar region, but rare in the thoracic spine. In this study, we first used a different percutaneous UBE “cave-in” decompression technique for the treatment of beak-type TOPLL. Methods A 31-year-old female with distinct zonesthesia and numbness below the T3 dermatome caused by beak-type TOPLL (T2–T3) underwent a two-step UBE decompression procedure. In the first step, the ipsilateral lamina, left facet joint, partial transverse process, and pedicles of T2 and T3 were removed. In the second step, a cave was created by removing the posterior third of the vertebral body (T2–T3). The eggshell-like TOPLL was excised by forceps, and the dural sac was decompressed. All procedures are performed under endoscopic guidance. A drainage tube was inserted, and the incisions were closed after compliance with the decompression scope via a C-arm. The patient's preoperative and postoperative radiological and clinical results were evaluated. Results Postoperative CT and MR films conformed complete decompression of the spinal cord. The patient's lower extremity muscle strength was greatly improved, and no complications occurred. The mJOA score improved from 5 to 7, with a recovery rate of 33.3%. Conclusion UBE spinal decompression for TOPLL showed favorable clinical and radiological results and offers the advantages of minimal soft tissue dissection, shorter hospital stays, and a faster return to daily life activities.